Entre brejos, grotas e chapadas: o campesinato sertanejo e o extrativismo do pequi nos cerrados de Minas Gerais - Marcos Nicolau Santos da Silva (2011)
The Brazilian Cerrado is rich in biodiversity of flora and fauna. Several are the population in their various environments, which make use mainly of its resources vegetables. Among the vegetables riches, find in the Cerrado, the extraction of pequi as an important activity that stimulates the economy in country and city. In this sense, the North of Minas Geraisstands out on the national stage of extraction of pequi. Besides the economic importance, the relevance pequi also has food, ecological and cultural. The Vale of Jequitinhonha also has significant production pequi, although this potential is underused. Therefore, the main objective of this study is to analyze the strategies agroextractivists, especially regarding the pequi, used by peasants in territory of the Cerrado Region of North Minas Gerais and of the Vale of Jequitinhonha that act in a complementary way to agriculture. The main issue the research was know if the pequi is a common property resource in the territories studied.The areas of research include: a rural community Cabeceiras of Mangaé, in the municipality of Japonvar; rural communities Guarda Mór, Olho D'água, Riacho Dantas, Riacho dos Santos and the Vila São José, in Campo Azul; and the localities Cachoeira of Fanado and Cachoeira of Lagoa, in Minas Novas. The research used descriptive and experimental methods with the detailed description of the phenomenon, observation and field research. Was carry out 15 interviews in rural properties in each municipality, and the total sample consisted of 45 families. The material data collect was based on semistructured questionnaire with questions opened and closed; recording of interviews in order to know the history of peasants and places,;and record oral histories in the field daily, with the intention of obtaining a greater wealth of detail. The survey results indicate that the pequi is a common property resource in the territories studied, overlapping the private ownership of land. The usage rules pequi are therefore based from usual logics, setting a land of open and collective use. Besides additional income, the pequi to some sertanejospeasants of Japonvar and Campo Azul generates still extra money or is the main income for the year. In these two borough, was established the existence of middlemen between peasants and buyers of cities that explores the work of peasants pequi, imposing the local price of the fruit. In Minas Novas, marketing pequi is smaller and, yet, no significantproblems to the crossing, which suggests a higher investment in associations and cooperatives to increase production and marketing. In this borough, pequi has meant greater use of the exchange, unlike the situation Japonvar and Campo Azul. It suggest the conversion agroextrativista public lands of the Minas Novas covered with eucalyptus, as provided for in the Pro-pequi. Furthermore, it is necessary to make eco-productive activities based on sustainable exploitation of the Cerrados of Campo Azul to replace the charcoal production from native forest. Finally, advocates become pequi and its derivatives as a cultural heritage with backcountry record in the book of knowledge IPHAN.